Examining the Effects of Supervised Laboratory Instruction on Students' Motivation and Their Understanding of Chemistry - Mirtachew T. Ali; Annette Lykknes; Dawit T. Tiruneh (MDPI AG, 2023)
This paper examines the impact of supervised laboratory instruction (SLI) on grade 12 students' understanding of acid-base and solution chemistry topics in the context of Ethiopian secondary schools. A mixed-methods research design was employed, with a purposive sampling of 160 secondary students from six schools in Northwest Ethiopia. The students were divided into two groups: an experimental group (n = 76) and a control group (n = 84). The experimental group attended sessions that were designed based on self-regulated learning (SRL) strategies with SLI, and the control group attended regular instruction designed by the course teacher. Both quantitative and qualitative data were collected to explore the impacts of the experimental and control lessons on improving students' conceptual understanding and motivation. Descriptive and inferential statistics (for the quantitative data)and reflexive thematic analysis(for the qualitative data)were employed to analyse the data. The findings showed that the SLI-SRL teaching approach for the experimental group resulted in a significantly higher conceptual understanding of the selected chemistry topics than the regular instruction for the control group. In addition, participants from the experimental group indicated that the SLI approach enhanced their motivation towards chemistry. These findings suggest that improving high-school students' motivation and their conceptual understanding of chemistry requires paying attention to the lesson design.